If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying M(x + y) = k (x * M + y * M) = k (xM + yM) = k Solving xM + yM = k Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1yM' to each side of the equation. xM + yM + -1yM = k + -1yM Combine like terms: yM + -1yM = 0 xM + 0 = k + -1yM xM = k + -1yM Divide each side by 'M'. x = kM-1 + -1y Simplifying x = kM-1 + -1y
| 2x+1=Ax^2+A+Bx^2+Cx | | 3240=36(p+30) | | 110=x+2 | | 3y/6a | | 8n-20=3n+20 | | -(x-6)=4 | | 20y^2+16y-21=0 | | 2(3y^2+8)(3y^2-8)=0 | | 3q^2-7=0 | | f(x)=3x^2+36x+96 | | z^2-12z=-13 | | 8w^2-8w=-2 | | .5x^2-x-14=0 | | 6090=29*14*24 | | .5(x-2)(x)-14=0 | | 5p^2=-9p | | -x-2y-8x= | | 7500=4600(1+i)6 | | 9+7x+3x=29 | | f(x)=x^3+4x^2+7x-10 | | .5(x-2)(x)-6=0 | | 0=x^3+4x^2+7x-10 | | (7/8)/(-5/7) | | 3xy=9xy | | 5x+3-7x=8+3x | | (-7/6)/(-8/9) | | 2.5+1.1=5.9 | | 28x^3-20x^2+63x-45= | | (2x-7)(x+4)=2x^2+8xy-7x-28y | | -4x+8=2x-9 | | 2.19-2.54x=3x-4.735 | | 7(x-9)-3=2(x-9)+17 |